2017
DOI: 10.17221/350/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant properties of some commercial honeys available on the Polish market

Abstract: Makarewicz M., Kowalski S., Lukasiewicz M., Małysa-Paśko M. (2017): Antimicrobial and antioxidant properties of some commercial honeys available on the Polish market. Czech J. Food Sci., 35: 401-406.Six commercial natural honeys available on the Polish market were characterised with respect to their geographical and floral origins, physicochemical parameters and microbial properties. The study focused on a determination of the activity of the main enzymes, antioxidant capacity and identification of antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…The predominance of fructose over glucose and glucose over maltose in our result was in line with the finding by Makarewicz et al 16 Although the concentration of both sugars varies depending on the botanical and entomological origin of the honey, it is generally expected that fructose will be found in a higher proportion than glucose and maltose 18 .…”
Section: Physiochemical Composition Between Honey Types Sugar Profilesupporting
confidence: 93%
See 1 more Smart Citation
“…The predominance of fructose over glucose and glucose over maltose in our result was in line with the finding by Makarewicz et al 16 Although the concentration of both sugars varies depending on the botanical and entomological origin of the honey, it is generally expected that fructose will be found in a higher proportion than glucose and maltose 18 .…”
Section: Physiochemical Composition Between Honey Types Sugar Profilesupporting
confidence: 93%
“…Comparably, this means the value was close to the result reported by Melaku and Tefera 11 (29.89±5 mEq kgG 1 ) and Alemu et al 20 (27.34±5.06 mEq kgG 1 ). However, the mean free acidity of ours was by far higher than the honey (A. mellifera) obtained from Nigeria 23 (18.67±0.64 mEq kgG 1 ) and the Polish market 16 (14.40±0.58 mEq kgG 1 ). Free acidity indicates one of the quality parameters of honey samples and it reveals whether the honey is fermented or not 27 and corresponds to the presence or absence of organic acids in the product.…”
Section: Moisture Content (Mc) Free Acidity (Fa) and Phcontrasting
confidence: 70%
“…In recent years, some studies have been published which analyze the quality of honeys collected from markets (Bhuvaneswari et al, 2014;Makarewicz et al, 2017;Aljohar et al, 2018;Mondragón-Cortez et al, 2019) and which compare the quality of honeys from markets with honeys directly from beekeepers (Bušová and Kouřimská, 2018;Hoxha et al, 2019;Aypak et al, 2019). Published results of market honeys most often point to the detected higher or above-limit HMF content and low diastase activity (Makarewicz et al, 2017;Aypak et al, 2019;Hoxha et al, 2019;Mondragón-Cortez et al, 2019) or above-limit water content (Hoxha et al, 2019). Aypak et al (2019) determined statistically most significant difference (p < 0.01) between HMF content and diastase activity between beekeeper and market honeys from Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, close findings were reported in Tigray (29.895 meq/kg; Gebreegziabher et al [ 38 ] and Amhara (27.34 meq/kg; Alemu et al [ 21 ]). However, the free acidity of honey from our study was higher than that of honey from Nigeria (18.67 0.64 meq/kg) [ 75 ] and the Polish market (14.40 ± 0.58 meq/kg) [ 76 ]. Muli et al [ 77 ] also reported free acidity ranging from 8 to 71.9 meq/kg in samples of honey collected from traditional processors, beekeepers, and honey traders in Kenya.…”
Section: Resultsmentioning
confidence: 60%